1983
DOI: 10.1177/088840648300600103
|View full text |Cite
|
Sign up to set email alerts
|

Changing Teachers' Perceptions of Mainstreaming

Abstract: A questionnaire was administered pre and post-test to 154 regular classroom teachers enrolled either in an in service program or in university courses designed to prepare regular classroom teachers to teach handicapped children mainstreamed into their classes. The questionnaire explored the teachers' beliefs and perceptions about mainstreaming in the areas of teaching skills, time available to teach handicapped children, attitudes toward mainstreaming, availability of materials, support services, and need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Resistance to new instructional approaches may be caused by insufficient knowledge of handicapping conditions (McGinty & Keogh, cited in Hudson, Reisberg, & Wolf, 1983), attribution of student difficulties to internal pathology (Medway, 1979), lack of skill in implementing instructional strategies (Hawryluk & Smallwood, 1986;Nevin, Paolucci-Whitcomb, Duncan, & Thibodeau, 1982), or concerns about teacher accountability (Heron & Harris, 1987). In these instances classroom teachers may envision failure.…”
Section: Expectation and Assistancementioning
confidence: 98%
“…Resistance to new instructional approaches may be caused by insufficient knowledge of handicapping conditions (McGinty & Keogh, cited in Hudson, Reisberg, & Wolf, 1983), attribution of student difficulties to internal pathology (Medway, 1979), lack of skill in implementing instructional strategies (Hawryluk & Smallwood, 1986;Nevin, Paolucci-Whitcomb, Duncan, & Thibodeau, 1982), or concerns about teacher accountability (Heron & Harris, 1987). In these instances classroom teachers may envision failure.…”
Section: Expectation and Assistancementioning
confidence: 98%
“…Also, Idol-Maestas and Ritter (1985) reported that some 22% of recent graduates from a consultant preparation program found colleagues resistant to consultation. Other studies have shown that regular educators perceive themselves as lacking skills and needing assistance to successfully implement mainstreaming (Hudson, Reisberg, & Wolf, 1983;Ryor, 1978).…”
Section: The Need For Consultationmentioning
confidence: 99%
“…However, there are continued doubts and concerns about the feasibility of successful mainstreaming, given existing levels of human and material resources, teacher training, and on-site consultation (Gans, 1984;Hudson, Reisberg, &Wolf, 1983;Mesinger, 1985).…”
mentioning
confidence: 98%